Answer:
(-3, 3)
Step-by-step explanation:
A graphing calculator shows the vertex to be (-3, 3).
__
You can rearrange the equation to vertex form:
y +2x +3 = -(x +2)^2 +1
y = -(x^2 +4x +4) +1 -2x -3 . . . . . . subtract 2x+3
y = -x^2 -6x -6 . . . . . . . . . . . . .collect terms
y = -(x^2 +6x) -6 . . . . . . . . . . . factor first pair
y = -(x^2 +6x +9) -6 +9 . . . . . add and subtract -9
y = -(x +3)^2 +3 . . . . . . . . . . . vertex form
In vertex form y=a(x-h)^2+k, the vertex is (h, k). Here, that is (-3, 3).
The vertex of the graph of this equation will be at point (x, y) = (-3, 3).